Multimorbidity and its associated factors among adults aged 50 and over: A cross-sectional study in 17 European countries. - Dyego Leandro Bezerra de Souza; Albert Oliveras-Fabregas; Albert Espelt; Marina Bosque-Prous; Marianna de Camargo Cancela; Ester Teixidó-Compañó; Javier Jerez-Roig (PLoS ONE)
Aims To estimate the prevalence of multimorbidity among European community-dwelling adults, as well as to analyse the association with gender, age, education, self-rated health, loneliness, quality of life, size of social network, Body Mass Index (BMI) and disability. Methods A cross-sectional study based on wave 6 (2015) of the Survey of Health, Ageing and Retirement in Europe (SHARE) was conducted, and community-dwelling participants aged 50+ (n = 63,844) from 17 European countries were selected. Multimorbidity was defined as presenting two or more health conditions. The independent variables were gender, age group, educational level, self-rated health, loneliness, size of network, quality of life, BMI and disability (1+ limitations of basic activities of daily living). Poisson regression models with robust variance were fit for bivariate and multivariate analysis. Results The prevalence of multimorbidity was 28.2% (confidence interval-CI 95%: 27.5.8-29.0) among men and 34.5% (CI95%: 34.1-35.4) among women. The most common health conditions were cardiometabolic and osteoarticular diseases in both genders, and emotional disorders in younger women. A large variability in the prevalence of multimorbidity in European countries was verified, even between countries of the same region. Conclusions Multimorbidity was associated with sociodemographic and physical characteristics, self-rated health, quality of life and loneliness.